GENESIS OF STRATIFORM PB-ZN DEPOSITS IN CARBONATE ROCKS: A HYDROGEOCHEMICAL APPROACH - Ryzhenko B.N.; Kraǐnov S.R. (My University, 2004)
According to the model proposed for the genesis of Pb-Zn stratiform ore mineralization in carbonate strata, (a) ore-forming elements disseminated in carbonate rocks or contained in them in low concentrations are extracted by connate seawater of the stage of gypsum and halite deposition; (b) these elements are transported by mineralized fluid percolating through the carbonate rock to the discharge zone, where the fluid mixes with excess meteoric waters; and (c) the dilution of the mineralized fluid with meteoric water triggers the precipitation of sphalerite, galena, and other ore and gangue minerals. Carbonate rocks rich in organic matter are favorable for the formation of predominantly sphalerite ores. Fluorite and witherite precipitate at temperatures below 125°C.